Model Sistem Dinamik Distribusi Bantuan Logistik Bencana Banjir (Studi Kasus Banjir Kecamatan Dayeuhkolot, Kabupaten Bandung) (GEMA EKONOMI, 2022)
This research was conducted to analyze the process of distributing disaster logistical assistance to evacuation posts carried out by the Bandung Regency Regional Disaster Management Agency. The purpose of this study is to determine the distribution planning that must be carried out by BPDB Bandung Regency in orders to minimize delays in the process of distributing logictical assistance. The method used in this researce is descriptive quantitative. Data processing is carried out using anylogic applications with the help of Causal Loop Diagram & Stock Flow Diagrams. The results of this study state that the mode of transportation and the use of distribution time can affect the smooth process of distributing aid packages by making scenario modeling to determine distribution planning carried out by BPBD Bandung Regency in order to minimize delays in the process of distributing logistical assistance